High-refractive-index sulfur-containing oligomer, preparation method thereof and optical material composition
By introducing high-content S elements into high-fold sulfur-containing oligomers and combining click chemical reactions to prepare optical materials with high refractive index, the problem of reduced transparency of existing materials when introducing aromatic and sulfur atoms is solved, and a combination of high refractive index and good optical properties is achieved.
Patent Information
- Application Number
- CN202411937010.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
When existing high-refractive index optical materials introduce aromatic and sulfur atoms, they may lead to reduced optical transparency in the visible light range, and their overall performance is not ideal, limiting the application range of materials.
A high-refractive sulfur-containing oligomer is used, and a high S element content on its main chain is prepared by reacting a dimer compound or a monomer containing unsaturated groups at the end, combined with a click chemical reaction, to prepare a highly refractive oligomer.
The refractive index of the material is significantly improved to reach above 1.7, preferably 1.9, while maintaining good optical transparency and heat resistance, suitable for display devices, optical lenses and optical devices.
Smart Images

Figure BDA0005211741010000021 
Figure BDA0005211741010000022 
Figure BDA0005211741010000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical materials, and in particular relates to a high-refractive sulfur-containing oligomer and a preparation method thereof and an optical material composition. Background Art
[0002] High-performance optical materials are the cornerstone for achieving high performance, integration, and lightweight of advanced optical devices. They have extensive and important applications in the fields of electronic communications, automobiles and ships, medical equipment, aerospace, etc. Optical materials with high transparency and high refractive index are key materials for advanced optical devices.
[0003] At present, in the public data, there are usually three ways to prepare synthetic high refractive index materials: 1) inorganic-organic hybrid materials; 2) dispersing inorganic nanoparticles in organic polymer media; 3) pure organic polymer materials. Among them, due to the characteristics of light weight, impact resistance and processability of organic polymer materials, in various embodiments, they can show many advantages over inorganic materials, such as higher transparency, suitable for thick films (from 1 micron to the order of centimeters), low shrinkage, mild processing conditions and longer shelf life. Therefore, it is a common method to prepare high refractive index materials by customizing chemical groups with high molar refractive index and low molar volume in the polymer structure to increase the refractive index of the polymer. In some embodiments, the introduction of halogen atoms (excluding fluorine), aromatic rings and sulfur increases the refractive index of the polymer. However, in some cases. Aromatic and sulfur atoms may also have unwanted side effects. For example, the optical transparency in the visible light range is reduced, and the comprehensive performance is not very ideal, which limits the application range of the material. Therefore, the synthesis of high-performance optical materials has become an inevitable trend. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, the present invention provides a high-refractive sulfur-containing oligomer and a preparation method thereof and an optical material composition.
[0005] The technical solution provided by the present invention is as follows:
[0006] A high-fold sulfur-containing oligomer comprises a repeating unit represented by the following formula 1:
[0007]
[0008] R1 and R2 are the same or different and are selected from the structural formula shown in Formula 2 or Formula 3:
[0009]
[0010] At least one of R1 and R2 is selected from the structural formula shown in Formula 3;
[0011] X is an ester group, a thiol ester group, an alkyleneoxy group having 1 to 15 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or an aryl group having 6 to 24 carbon atoms;
[0012] R3 is H, OH or methyl;
[0013] R4 and R5 are selected from a cycloalkyl group having 3 to 20 carbon atoms, a heterocycloalkyl group having 3 to 20 carbon atoms containing any one or more heteroatoms selected from N, O and S, and a cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms;
[0014] R4 and R5 are each independently substituted by m R', where m is greater than or equal to zero (0 or a natural number, such as 1, 2, 3, 4, 5, 6), and the R' is selected from a hydroxyl group, a cyano group, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 24 carbon atoms, and a cycloalkyl group having 3 to 10 carbon atoms.
[0015] The degree of polymerization of the oligomer is n=10-20.
[0016] The terminal groups of the oligomers are thiol groups or double bonds.
[0017] The S content on the main chain of the above oligomer is relatively high, which greatly improves the refractive index.
[0018] Preferably, at least one of R1 and R2 has: at least one structural unit of a heterocycloalkyl group having 3 to 20 carbon atoms and selected from N, O and S heteroatoms, or a cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms.
[0019] Preferably, in the technical solution of the present application, the cycloalkyl group having 3 to 20 carbon atoms is preferably a saturated cycloalkyl group of C5-C10; more preferably a saturated cycloalkyl group of C5-C7.
[0020] Preferably, in the technical solution of the present application, the cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms is preferably a monocyclic unsaturated hydrocarbon group having 5 to 8 carbon atoms or a polycyclic unsaturated hydrocarbon group having 10 to 24 carbon atoms.
[0021] Furthermore, the formula 2 specifically has the structural formulas shown in 2-1 and 2-2:
[0022]
[0023] R3, R4, and R5 have the definitions given above; preferably, in formula 2-2, R4 is selected from the cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms and having at least one S in the heterocyclic ring.
[0024] Preferably, in the technical solution of the present invention, more preferably, the oligomer is of the structural formula shown in 2-1.
[0025] Furthermore, the cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms has the structural formula shown in A-1, A-2, and A-3. Z is selected from a nitrogen atom, a sulfur atom or C-R8, wherein R8 is selected from a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 5 to 30 carbon atoms, a heterocycloalkyl group having 5 to 30 carbon atoms and at least one selected from N, O and S; and Ar1 is selected from space, a cycloalkyl group having 4-6 carbon atoms or an aryl group having 6-18 carbon atoms.
[0026] R6 and R7 are selected from empty, single bond, O, S, -N(R9)-, -S(=O)2-, substituted or unsubstituted alkylene with 1 to 5 carbon atoms, R6 and R7 are not empty or single bond at the same time; R9 is selected from alkyl with 1 to 5 carbon atoms.
[0027] Among them, any one or more H on the benzene ring in the structural formulas represented by A-1, A-2, and A-3 can be replaced by one or more R', and R' is selected from hydroxyl, cyano, alkyl having 1 to 10 carbon atoms, aryl having 6 to 24 carbon atoms, and cycloalkyl having 3 to 10 carbon atoms.
[0028] More preferably, R' is selected from an alkyl group having 1 to 3 carbon atoms, or A-1, A-2, A-3 are unsubstituted.
[0029] In formula A-1, preferably, at least one Z is selected from S atom. Said A-1 is selected from one of the following:
[0030]
[0031] In formula A-2, preferably, Ar is preferably argon or phenyl.
[0032] Further, the A-3 is selected from one of the following:
[0033] Furthermore, the at least one heterocyclic ring of the heterocycloalkyl group having 3 to 20 carbon atoms selected from N, O and S contains at least 1 to 2 S atoms as substitutions.
[0034] Preferably, in the technical scheme of the present application, at least one heterocycloalkyl group having 3 to 20 carbon atoms selected from N, O and S heteroatoms is preferably a heterocycloalkyl group having 3 to 8 carbon atoms, and at least one H is substituted by a S atom.
[0035] Preferably, at least one heterocycloalkyl group having 3 to 20 carbon atoms and selected from N, O and S heteroatoms is selected from a five-membered ring or a six-membered ring substituted with at least one S atom.
[0036] Furthermore, the formula 1 is specifically the structural formula shown in 1-1 and 1-2:
[0037]
[0038] Furthermore, the high-fold sulfur-containing oligomer has the following structural formula:
[0039]
[0040]
[0041] In a second aspect, the present invention provides a method for preparing a high-fold sulfur-containing oligomer, comprising the following steps: mixing a monomer having a structural unit shown in Formula 3, or mixing a monomer having a structural unit shown in Formula 3 with a monomer having a structural unit shown in Formula 2 in a solvent, heating and stirring, and collecting the reaction liquid to obtain a high-fold sulfur-containing oligomer.
[0042] In a third aspect, an optical material composition comprises the high-refractive sulfur-containing oligomer.
[0043] In a fourth aspect, a high-refractive sulfur-containing oligomer is used, wherein the optical material composition is applied to display devices, optical lenses and optical devices.
[0044] The technical solution of the present invention is adopted, a dithiol compound or a monomer containing an unsaturated group at the end is reacted, and a click chemistry reaction between thiol groups or between thiol groups and double bonds is adopted to obtain a highly refractive oligomer. After the reaction is completed, the S element will be retained on the main chain. The S element content in the finally obtained oligomer is very high, so that the refractive index is greatly improved, specifically above 1.7, preferably reaching 1.9. Secondly, the monomer containing an unsaturated group contains a large number of benzene rings, so the resin obtained after the reaction contains a large number of rigid benzene ring structures, so the optical resin obtained has good heat resistance. Finally, the oligomer of the technical solution of the present invention has good compatibility with inorganic nanoparticles, so that the inorganic nanoparticles are evenly dispersed in the composition, and have good storage stability, so that the composition has a high refractive index while having good mechanical properties and optical properties. DETAILED DESCRIPTION
[0045] The principles and features of the present invention are described below. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0046] In the examples of the present invention, the degree of polymerization of the oligomers is n=10-20. Molecular weight Mw determination, reference sample: polystyrene, mobile phase: THF, flow rate: 1 ml / min.
[0047] Embodiment 1:
[0048]
[0049] In a 50 ml flask, (1.42 g, 10 mmol) A1 (CAS: 624-39-5) and (0.18 g, 1 mmol) B1 (CAS: 153729-30-7) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S1 with a molecular weight of Mw = 4772.
[0050] Embodiment 2:
[0051]
[0052] In a 50 ml flask, (2.62 g, 10 mmol) A2 (CAS: 7344-22-1) and (0.15 g, 10 mmol) B2 (CAS: 22511-31-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S2 with a molecular weight Mw = 5686.
[0053] Embodiment 3:
[0054]
[0055] In a 50 ml flask, (1.50 g, 10 mmol) A3 (CAS: 132120-63-9) was dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S3 with a molecular weight Mw = 5034.
[0056] Embodiment 4:
[0057]
[0058] In a 50 ml flask, (1.48 g, 10 mmol) A4 (CAS: 22511-31-5) and (0.37 g, 1 mmol) B4 (CAS: 1359657-36-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S4 with a molecular weight of Mw = 6736.
[0059] Embodiment 5:
[0060]
[0061] In a 50 ml flask, (1.49 g, 10 mmol) A5 (CAS: 540-63-6) and (0.37 g, 1 mmol) B5 (1359657-36-5) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S5 with a molecular weight of Mw = 7787.
[0062] Embodiment 6:
[0063]
[0064] In a 50 ml flask, (1.84 g, 10 mmol) A6 (CAS: 645404-26-8) and (0.35 g, 1 mmol) B6 (CAS: 103489-89-0) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S6 with a molecular weight of Mw = 7534.
[0065] Embodiment 7:
[0066]
[0067] In a 50 ml flask, (1.5 g, 10 mmol) A7 (CAS: 127522-05-8) and (0.31 g, 1 mmol) B7 (CAS: 68678-73-9) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was spin-dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S7 with a molecular weight of Mw = 6900.
[0068] Embodiment 8:
[0069]
[0070] In a 50 ml flask, (1.5 g, 10 mmol) A8 (CAS: 132120-63-9) and (0.31 g, 1 mmol) B8 (CAS: 1426222-40-3) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S8 with a molecular weight Mw = 7058.
[0071] Embodiment 9:
[0072]
[0073] In a 50 ml flask, (1.5 g, 10 mmol) A9 (CAS: 132120-63-9) and (0.36 g, 1 mmol) B9 (CAS: 103489-89-0) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S9 with a molecular weight Mw = 7562.
[0074] Embodiment 10:
[0075]
[0076] In a 50 ml flask, (1.5 g, 10 mmol) A10 (CAS: 132120-63-9) and (0.34 g, 1 mmol) B10 (CAS: 2425533-68-0) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S10 with a molecular weight of Mw = 7772.
[0077] Embodiment 11:
[0078]
[0079] In a 50 ml flask, (1.5 g, 10 mmol) A11 (CAS: 132120-63-9) and (0.46 g, 1 mmol) B11 (CAS: 1232504-88-9) were dissolved in 20 ml tetrahydrofuran and stirred at room temperature for 4 h. The reaction status of the raw materials was confirmed by TLC spot plate, and the molecular weight of the polymer was detected by GPC. After the reaction was completed, the solvent tetrahydrofuran was dried to obtain a polymer powder, which was washed with ethanol and deionized water in turn and vacuum dried to obtain S11 with a molecular weight of Mw = 7598 。
[0080] Performance testing:
[0081] The refractive index and extinction coefficient were measured by Abbe refractometer; the glass transition temperature was measured by differential scanning calorimetry (DSC), the measuring conditions were nitrogen, the temperature range was -40°C to 100°C, and the heating rate was 10°C / min; the thermal stability analysis was measured on Shimadzu TGA-50 thermal analyzer, nitrogen, the heating rate was 20°C / min, and the test temperature range was 40°C to 550°C; the test results are shown in Table 1 below:
[0082] Table 1
[0083]
[0084] It can be seen from the above table that the high-refractive sulfur-containing oligomer obtained in the embodiment of the technical solution of the present invention has a refractive index of more than 1.8 and can be as high as 1.9, and has a high refractive index, good optical properties such as extinction coefficient, and a glass transition temperature of more than 160°C, with good heat resistance.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-fold sulfur-containing oligomer, characterized in that: It includes a repeating unit represented by the following formula 1: R1 and R2 are the same or different and are selected from the structural formula shown in Formula 2 or Formula 3: At least one of R1 and R2 is selected from the structural formula shown in Formula 3; X is an ester group, a thiol ester group, an alkyleneoxy group having 1 to 15 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or an aryl group having 6 to 24 carbon atoms; R3 is H, OH or methyl; R4 and R5 are selected from a cycloalkyl group having 3 to 20 carbon atoms, a heterocycloalkyl group having 3 to 20 carbon atoms containing any one or more heteroatoms selected from N, O and S, and a cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms; R4 and R5 are each independently substituted by m R', m is greater than or equal to zero, and the R' is selected from hydroxyl, cyano, alkyl having 1 to 10 carbon atoms, aryl having 6 to 24 carbon atoms, and cycloalkyl having 3 to 10 carbon atoms.
2. The high-refractive sulfur-containing oligomer according to claim 1, characterized in that The formula 2 is specifically the structural formula shown in 2-1 and 2-2: In formula 2-2, R4 is selected from the cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms and having at least one S in the heterocyclic ring.
3. The high-refractive sulfur-containing oligomer according to claim 1, characterized in that: In R4 and R5, the cyclic unsaturated hydrocarbon group having 5 to 24 carbon atoms has the structural formula shown in A-1, A-2, and A-3: Z is selected from a nitrogen atom, a sulfur atom or CR8, wherein R8 is selected from a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 5 to 30 carbon atoms, a heterocycloalkyl group having 5 to 30 carbon atoms or at least one heteroatom selected from N, O and S; The Ar1 is selected from a null, a cycloalkyl group having 4 to 6 carbon atoms or an aryl group having 6 to 18 carbon atoms; R6 and R7 are selected from a blank, a single bond, O, S, -N(R9)-, -S(=O)2-, a substituted or unsubstituted alkylene group having 1 to 5 carbon atoms, and R6 and R7 are not blank or a single bond at the same time; R9 is selected from an alkyl group having 1 to 5 carbon atoms; Among them, any one or more H on the benzene ring in the structural formulas shown in A-1, A-2, and A-3 can be replaced by one or more of the R's.
4. The high-refractive sulfur-containing oligomer according to claim 3, characterized in that: The A-1 is selected from one of the following:
5. The high-refractive sulfur-containing oligomer according to claim 3, characterized in that: The A-3 is selected from one of the following:
6. The high-refractive sulfur-containing oligomer according to claim 1, characterized in that: R4 and R5 are selected from the heterocyclic alkyl groups having 3 to 20 carbon atoms and containing at least one or two S in the heterocyclic ring.
7. The high-refractive sulfur-containing oligomer according to claim 1, characterized in that: The formula 1 is specifically the structural formula shown in 1-1 and 1-2:
8. The high-refractive sulfur-containing oligomer according to claim 1, characterized in that: The high-fold sulfur-containing oligomer has the following structural formula:
9. A method for preparing a high-refractive sulfur-containing oligomer according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing a monomer having a structural unit shown in Formula 3 in a solvent, or mixing a monomer having a structural unit shown in Formula 3 and a monomer having a structural unit shown in Formula 2 in a solvent, heating and stirring, collecting the reaction liquid, and purifying to obtain the high-fold sulfur-containing oligomer.
10. An optical material composition, characterized in that: At least comprising the high-fold sulfur-containing oligomer according to any one of claims 1 to 8.